2013
DOI: 10.1071/ch12393
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product-Inspired Pyranonaphthoquinone Inhibitors of Indoleamine 2,3-Dioxygenase-1 (IDO-1)

Abstract: A series of pyranonaphthoquinone derivatives possessing structural features present in both natural products annulin B and exiguamine A have been shown to exhibit low micromolar inhibition of indoleamine 2,3-dioxygenase-1 (IDO-1). These inhibitors retain activity against the enzyme in a cellular context with an approximate one-log loss of dose potency against IDO-1 in cells. One particular analogue, triazole 8 shows good inhibition of IDO-1 along with little loss of cell viability at low drug concentrations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Another study has suggested that pyranonaphthoquinone-based compounds possess dual IDO1 and topoisomerase II inhibitory activity, thus inhibiting cell growth of human H460 cells. 54,55 Compounds that integrate tumoricidal activity along with IDO1 inhibitory activity may produce substantially more robust single-agent antitumor responses than IDO1 inhibitors that do not exert a cytotoxic effect. Naphthoquinone-based compounds are reported to act as direct small-molecule inhibitors of signal transducer and activator of transcription 3 (STAT3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another study has suggested that pyranonaphthoquinone-based compounds possess dual IDO1 and topoisomerase II inhibitory activity, thus inhibiting cell growth of human H460 cells. 54,55 Compounds that integrate tumoricidal activity along with IDO1 inhibitory activity may produce substantially more robust single-agent antitumor responses than IDO1 inhibitors that do not exert a cytotoxic effect. Naphthoquinone-based compounds are reported to act as direct small-molecule inhibitors of signal transducer and activator of transcription 3 (STAT3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the present study, galanal was found to possess more IDO1 inhibitory potency than either the most-commonly used 1-MT or other previously-published inhibitors ( Table. 1 ) [14] [28] [34] [35] [36] [37] [38] [39] [40] [41] [42] [43] . Since the IC 50 value of inhibitor depends on the IDO1 enzyme activity in each experiment, we could not unconditionally compare the previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the outstanding immune-modulate properties of IDO1, IDO1 inhibitors have been searched for in many fields, to control various inflammatory diseases. Thus, it is hoped that the inhibitor of IDO1 becomes the new therapeutic target for drugs corresponding to various inflammatory diseases [13] [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Together with inhibitors' bound structures, the crystal structure of substrate bound state, recently resolved, brings an opportunity to develop new rationales on the development of IDO1 inhibitors. Therefore, even though great efforts have been made to develop IDO1 inhibitors using structure‐based design, high throughput screening (HTS) and natural product screening are still ongoing and successfully yielded different active scaffolds …”
Section: Indoleamine 23‐dioxygenase1mentioning
confidence: 99%